Kitab al-Bayan wa al-Tabyin Karya Al-Jahiz: Kajian Semiotik tentang Retorika Arab dan Makna Tanda-Tanda Budaya di Era Klasik - Miftahur Rahman el-Banjary (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The book al-Bayan wa al-Tabyin by Al-Jahiz is one of the monumental works in the history of classical Arabic literature that discusses rhetoric, communication, and Arab culture. This study aims to examine the semiotic meaning in Arabic rhetoric and cultural signs contained in the book, as well as its relevance in understanding the evolution of Arabic communication. The benefits of this study are to provide deeper insights into the interaction between language, culture, and rhetorical systems, as well as to explore how this classic work can contribute to contemporary communication studies. The research method used is library research with a descriptive qualitative approach, which involves analyzing Al-Jahiz's texts and cultural context and collecting data from various relevant literary sources. The results of the study show that Kitab al-Bayan wa al-Tabyin not only describes the classical Arabic rhetorical system but also reflects the complex relationship between culture, language, and social signs. This study provides a new perspective on how classical traditions can be reinterpreted to understand the evolution of Arabic communication in the modern era. Thus, this study contributes to the development of semiotics and rhetoric studies in the context of Arab culture.